Depression, Anxiety and Their Correlates Among Patients With HIV in South Ethiopia: An Institution-Based Cross-Sectional Study - Duko, Bereket; Toma, Alemayehu; Asnake, Solomon; Abraham, Yacob (Frontiers in Psychiatry, 2019)
Background: Depressive and anxious symptoms are regularly seen in HIV infected people than the all-inclusive community. This investigation planned to evaluate the magnitude and factors related to depressive and anxiety symptoms among HIV patients in South Ethiopia, 2018. Methods: An institution-based cross-sectional study directed among 363 HIV infected individuals who had a customary visit at Hawassa University Comprehensive Specialized Hospital and Yirgalem Hospital, Ethiopia, who were incorporated into the study through systematic sampling techniques. Hospital anxiety and depression scale (HADS) utilized to take a look at anxious and depressive symptoms. Results: The mean age of the respondents was 37.66 years (SD ±10.03). Prevalence of depression and anxiety were 32.0% and 34.4% respectively. Patients who were living alone [AOR=1.94, (95% CI: 1.06, 3.56)], poor social support [AOR=5.57, (95% CI: 1.20, 10.84)] & HIV related perceived stigma [AOR=2.35, (95% CI: 1.44, 3.84)] were more likely to have depression as compared to their counterparts. Having the previous history of mental illness [AOR=3.36, (95% CI: 1.31, 8.61)] & poor social support [AOR=6.67, (95% CI: 1.47, 10.33)] were more likely to have anxiety symptoms. Conclusion: prevalence of anxiety and depression in the current study was high. Concerned health departments of the country should create guidelines to screen and treat depression and anxiety among HIV patients. Further research on hazard factors of depression and anxiety ought to be examined to fortify and expand these findings.